Molecular data attest to the occurrence of autochthonous Daphnia pulex (Crustacea, Branchiopoda) populations in Sicily, Italy - Luca Vecchioni; Marco Arculeo; Federico Marrone (Advances in Oceanography and Limnology)
Biological invasions are known to be among the most important threats to the long-term conservation of native biota, and their effects might be even more difficult to contrast when they are cryptic, i.e., when the non-native invaders cannot be easily recognised based on morphology, and can thus be confused with native taxa. Such cryptic invasions are known to widely occur in the cladoceran genus Daphnia O.F. Müller, 1785, so that the actual distribution and status of most species and lineages need to be checked with a genetic approach. In the frame of this work, we investigated if the Sicilian populations of D. (Daphnia) pulex Leydig, 1860 belonged to the allochthonous North American lineage, which is known to occur in several regions of the Palearctic and Afrotropical biogeographical regions, or rather to the autochthonous European lineage of the species. The molecular results obtained, based on a fragment of the mitochondrial gene encoding for NADH subunit dehydrogenase 5 (ND5), allowed us to rule out the allochthonous status of the species, confirming the presence of autochthonous relictual lineages of D. pulex in Sicily. The native status of these populations is in agreement with their local distribution, limited to natural and poorly-impacted water bodies mostly located in wooded areas at medium and high altitudes. The current local distribution of D. pulex in Sicily is possibly linked to the end of the last glacial maximum and the onset of warmer climatic conditions in the early Holocene, which led the species to take refuge in colder microthermal refugia located at high altitudes, determining their current relictual distribution.